2012
DOI: 10.3389/fphys.2012.00337
|View full text |Cite
|
Sign up to set email alerts
|

Period2 gene mutant mice show compromised insulin-mediated endothelial nitric oxide release and altered glucose homeostasis

Abstract: Period2 (Per2) is an important component of the circadian clock. Mutation of this gene is associated with vascular endothelial dysfunction and altered glucose metabolism. The aim of this study is to further characterize whole body glucose homeostasis and endothelial nitric oxide (NO) production in response to insulin in the mPer2Brdm1 mice. We show that mPer2Brdm1 mice exhibit compromised insulin receptor activation and Akt signaling in various tissues including liver, fat, heart, and aortas with a tissue-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 35 publications
2
24
0
1
Order By: Relevance
“…Similar to previous reports, we demonstrated significantly lower temperature amplitude and stability in our obese group of subjects (Corbalán-Tutau et al, 2011). We also concurred with previous findings (Atkinson et al, 2007; Carvas et al, 2012; Colwell & Matveyenko, 2014; Garaulet & Gomez-Abellan, 2014) that several physiological and behavioral measures were significantly associated with circadian rhythm parameters when the total group, and adiposity groups were examined separately. It was interesting to note that we detected changes in circadian amplitude and stability parameters in subjects with only one MetS risk factor compared to those with no MetS factors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to previous reports, we demonstrated significantly lower temperature amplitude and stability in our obese group of subjects (Corbalán-Tutau et al, 2011). We also concurred with previous findings (Atkinson et al, 2007; Carvas et al, 2012; Colwell & Matveyenko, 2014; Garaulet & Gomez-Abellan, 2014) that several physiological and behavioral measures were significantly associated with circadian rhythm parameters when the total group, and adiposity groups were examined separately. It was interesting to note that we detected changes in circadian amplitude and stability parameters in subjects with only one MetS risk factor compared to those with no MetS factors.…”
Section: Discussionsupporting
confidence: 91%
“…This may result in a desynchronization or misalignment of the central and peripheral clocks with associated disruption in organ and system circadian rhythms. Studies have demonstrated that forced desynchrony in humans and rodents is associated with significant adverse changes in risk factors for cardiometabolic disease (Barclay et al, 2012; Carvas et al, 2012; Froy, 2010; Garaulet & Madrid, 2009; Marcheva et al, 2010; Muller et al, 1985). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, their glucose and lipid metabolism is disturbed, resulting in hyperglycemia, hypoinsulinemia, and hyperlipidemia. Like the Clock-d19 mice, Per2 Brdm1-/-mice also show a mania-like behavior, arrhythmic food intake, hyperphagia, and, at least in the first four months of their life, increased body weight [72][73][74][75]. However, unlike Clock-d19 mice, they These studies show that genetic perturbations of circadian rhythms simultaneously alter both mood regulation and central metabolic functions.…”
Section: Clock Gene Mutations Affect Mood-related Behavior and Metabomentioning
confidence: 88%
“…Similarly, Per2 mutant mice have lower body fat content and total body weight, and show aberrations in blood glucose regulation, with fasting hypoglycemia, impaired gluconeogenesis and increased insulin sensitivity despite being hyperinsulinemic [102]. Rev-erbα -/-animals have increased white adipose tissue, elevated blood glucose, decreased blood lipid levels, and abnormal bile acid levels [103,104].…”
Section: The Circadian Clock and Energy Metabolismmentioning
confidence: 98%